Aminoacylation of Alkenes by Cooperative NHC and Photoredox Catalysis - Lezius, Lena; Reimler, Jannik; Döben, Nadine; Hamm, Michael; Daniliuc, Constantin G.; Studer, Armido (Synlett, 2023)
Cooperative NHC and photoredox catalysis has gained significant attention as an emerging research field in recent years. Herein, we report a cyclizing aminoacylation of alkenes, which is enabled through the combination of these two catalytic modes. The key step is a radical/radical cross-coupling between a persistent ketyl radical and a transient benzylic or aliphatic C-radical, which is generated through radical cyclization of an oxidatively formed amidyl radical. Several carbamates, amides and sulfonamides containing an alkene moiety and different acyl fluorides can be used as substrates. The resulting products are obtained in moderate to good yields.
Keywords: NHC catalysis; photoredox catalysis; radical cyclization; radical acylation; nitrogen radicals